Coaxial TP/APR electrospun nanofibers for programmed controlling inflammation and promoting bone regeneration in periodontitis-related alveolar bone defect models. (December 2022) - He, Ze; Liu, Shibo; Li, Zhongming; Xu, Jiazhuang; Liu, Yao; Luo, En
Abstract: Periodontitis is a pathological dental condition that damages the periodontal tissue and leads to tooth loss. Bone regeneration in periodontitis-related alveolar bone defects remains a challenge for periodontists and tissue engineers because of the complex periodontal microenvironment. The inflammatory microenvironment is associated with poor osteogenesis; therefore, the reduction of inflammation is essential for bone regeneration in periodontitis-related alveolar bone defects. Here, we developed a programmed core-shell nanofibers that allows the sequential and controlled release of tea polyphenols (TP) and AdipoRon (APR) to control inflammation and promote bone regeneration to repair periodontitis-related alveolar bone defects. Core-shell nanofibers with a sequentially controlled release function were synthesized using electrospinning. We investigated the therapeutic effects of the nanofibers in vitro and in a mouse periodontitis model. The results of the release profiles demonstrated that TP was released rapidly in the early stages and APR was continuously released thereafter. In vitro experiments showed that the programmed core-shell nanofibers reduced the levels of proinflammatory cytokines and increased osteogenic differentiation in an inflammatory microenvironment. In vivo experiments, the programmed core-shell nanofibers ameliorated periodontal tissue inflammation and improved alveolar bone regeneration. Our results indicated that the programmed core-shell nanofibers with a sequential-release function provides an ideal strategy for repairing periodontitis-related alveolar bone defects, and its application in the treatment of diseases with spatiotemporal specificity is promising. Graphical abstract: The sequential and controlled drug release system to coordinate the spatiotemporal specificity of the periodontitis bone remodeling process: firstly, the rapid release of TP in the shell layer inhibits the inflammation and reduces the bone resorption. Subsequently, the delayed and sustained release of APR in the core layer promotes the osteogenic differentiation of BMSCs, increasing the alveolar bone regeneration. Image 1